A Novel Online Estimation and Compensation Method for Strapdown Phased Array Seeker Disturbance Rejection Effect Using Extended State Kalman Filter - Shih-Yao Lin (IEEE Access, 2019)
The radome error and beam pointing error found commonly in the strapdown phased array radar seeker can cause coupling between the missile body motion and the seeker model, impacting the output precision of the seeker and causing the disturbance rejection effect (DRE). Aiming to address the serious impact of DRE on the missile guidance and control system, a strapdown phased array radar seeker DRE parasitic loop (considering radome error and beam pointing error) is established. The DRE parasitic loop is analyzed. The main aim of this paper was to develop a novel online estimation and compensation method for a DRE parasitic loop using an extended state Kalman filter, which was compared with an extended Kalman filter and a strong tracking unscented Kalman filter. The simulation results show that the proposed online estimation and compensation method for the DRE parasitic loop can estimate the radome error slope and beam pointing error slope stably and accurately from the initial velocity pointing error input and the large initial estimation error. Effective suppression of the DRE problem and compensation for the line-of-sight angular rate output in real time is achieved. Furthermore, the guidance system performance and precision are both improved.